AICCRA- Gender and Social Inclusion Workshop Report - Chanana, Nitya; Huyer, Sophia; Ma, Stephanie (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The report is a short summary of the two-day AICCRA Gender and Social Inclusion Workshop. The workshop was aimed at initiating the development of a streamlined approach to these gender activities across AICCRA and was attended by 36 participants. The sessions included discussions on the two case studies, a brief introduction the broad GSI components of AICCRA including gender integration across prioritization, implementation and monitoring & evaluation stages of the project and the GSI scaling framework. Additionally, all the six AICCRA country teams presented their GSI activities for the project.